Post-exposure prophylaxis to prevent varicella in immunocompromised children - Makoto Yamaguchi; Nobuyuki Tetsuka; Toshihiko Okumura; Kazunori Haruta; Takako Suzuki; Yuka Torii; Jun-ichi Kawada; Yoshinori Ito (Elsevier, 2022)
Summary: Background: Varicella-zoster virus (VZV) infection can cause life-threatening events in immunocompromised patients. Post-exposure prophylaxis (PEP) is required to prevent secondary VZV infection. Limited evidence is available for the use of acyclovir (ACV)/valacyclovir (VCV) as PEP. Methods: Herein, we retrospectively analyzed immunocompromised paediatric patients with significant exposure to VZV. Patients administered PEP were categorized into four groups: 1) ACV/VCV group; 2) intravenous immunoglobulin (IVIG) group; 3) ACV/VCV/IVIG group; 4) vaccine group. Results: Among 69 exposure events, 107 patients were administered PEP (91, ACV/VCV; 16, ACV/VCV/IVIG) and 10 patients did not receive PEP (non-PEP group). The index case was diagnosed based on clinical symptoms in 55 cases (79.7%). Fourteen cases (20.3%) were confirmed using direct virological diagnostic procedures. In the PEP group, only 2 patients (2.2%) developed secondary VZV infections. Additionally, 2 patients in the non-PEP group (20.0%) developed secondary VZV infection. The incidence of secondary VZV infection was significantly lower in the PEP group than in the non-PEP group (P=0.036). Among patients administered PEP, no antiviral drug-induced side effects were detected. Conclusions: Antiviral agents administered as PEP are effective and safe for preventing VZV infections in immunocompromised patients. Rapid virological diagnosis of index cases might allow efficient administration of PEP after significant exposure to VZV infection.